Tailored tetravalent antibodies potently and specifically activate Wnt/Frizzled pathways in cells, organoids and mice - Yuyong Tao; Monika Mis; Levi Blazer; Mart Ustav Jnr; Zachary Steinhart; Rony Chidiac; Elli Kubarakos; Siobhan O'Brien; Xiaomei Wang; Nick Jarvik; Nish Patel; Jarrett Adams; et al. (eLife, 2019)
Secreted Wnt proteins regulate development and adult tissue homeostasis by binding and activating cell-surface Frizzled receptors and co-receptors including LRP5/6. The hydrophobicity of Wnt proteins has complicated their purification and limited their use in basic research and as therapeutics. We describe modular tetravalent antibodies that can recruit Frizzled and LRP5/6 in a manner that phenocopies the activities of Wnts both in vitro and in vivo. The modular nature of these synthetic Frizzled and LRP5/6 Agonists, called FLAgs, enables tailored engineering of specificity for one, two or multiple members of the Frizzled family. We show that FLAgs underlie differentiation of pluripotent stem cells, sustain organoid growth, and activate stem cells in vivo. Activation of Wnt signaling circuits with tailored FLAgs will enable precise delineation of functional outcomes directed by distinct receptor combinations and could provide a new class of therapeutics to unlock the promise of regenerative medicine.